The Role of Pancasila in Preventing Hoaxes and Negative Content on Social Media - Tampubolon, Nadia Malika; Barus, Yerikho Loren; Simanullang, Yogi Setiawan (Lembaga Riset Mutiara Akbar, 2025)
Social media is often a place for spreading hoaxes and negative content that can damage social harmony. These fake messages can trigger tension, conflict, and distrust among various groups in society. Pancasila, as the ideological foundation of the Indonesian state, offers noble values ??that can be a guide in using social media ethically and responsibly. This study examines how the application of Pancasila values, such as honesty, justice, and unity, can help prevent the spread of false information or hoaxes and harmful content on social media. Honesty teaches us to convey information that is true and not misleading, while justice reminds us to act fairly and wisely in sharing information. The value of unity invites us to maintain the harmony and unity of the nation by avoiding the spread of content that can be divisive. The results of the study show that by internalizing Pancasila values ??such as honesty, justice, and unity, social media users can contribute to creating a positive and harmonious digital environment.